2020
DOI: 10.1108/f-02-2019-0026
|View full text |Cite
|
Sign up to set email alerts
|

Does facility management affect perception of building quality?

Abstract: Purpose This paper aims to examine the strategy, selection and perception of facility management (FM) services and the effect it may have on perceived building quality. Design/methodology/approach Data was collected through a survey distributed to board members of cooperatives for newly constructed buildings in Sweden. Responses from 394 cooperative boards were included in the data set and analysed. The difference in cooperative choice of FM strategy and satisfaction with FM services was examined with non-pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 82 publications
0
7
0
Order By: Relevance
“…The result is expected because financial resources are crucial for controlling the quality and functionality of properties and assets (Abd-Wahab et al, 2015;Gao & Ho, 2016;Rasip, 2017). A research in Sweden by Jonsson (2020) found that the residents' perception of building quality was the indicator of the housing cooperatives' effectiveness. In the local context, a study by Rasip (2017) revealed that the residents' payment attitude was affected by the quality of the management managing their HRS.…”
Section: Discussionmentioning
confidence: 99%
“…The result is expected because financial resources are crucial for controlling the quality and functionality of properties and assets (Abd-Wahab et al, 2015;Gao & Ho, 2016;Rasip, 2017). A research in Sweden by Jonsson (2020) found that the residents' perception of building quality was the indicator of the housing cooperatives' effectiveness. In the local context, a study by Rasip (2017) revealed that the residents' payment attitude was affected by the quality of the management managing their HRS.…”
Section: Discussionmentioning
confidence: 99%
“…Almost all the assets in the sample suffered from deficiencies in maintenance and repair, probably due to bad construction methods in the first place or huge turnover among occupants. Case studies have shown that problems with building defects have an influence on the building quality and customer satisfaction (Zalejska-Jonsson, 2020). Thus, cost saving in maintenance services may have the effect of lowering the quality of asset function, leading to further revenue loss.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to the condition of the building, maintenance considerations can also be taken from the building occupant satisfaction survey. According to Zalejska-Jonsson [36], in addition to building severity, the level of comfort felt by building occupants is also one of the determinants of building quality. Pontan et al [37] also showed that 68.65% of building maintenance effectiveness is affected by building occupant satisfaction.…”
Section: Building Maintenance Documentsmentioning
confidence: 99%